Genome-wide analysis of the CCCH zinc finger family in longan: Characteristic identification and expression profiles in Dimocarpus longan Lour - Li-yao SU; Xue-chen XIAO; Meng-qi JIANG; Shu-qi HUANG; Xiao-dong XUE; Xue LI; Zhong-xiong LAI; Yu-ling LIN (Journal of Integrative Agriculture, 2022)
CCCH (C3H) Zinc finger (Znf) transcription factors (TFs), as a novel type of Znf gene, regulate the expression of genes by binding to their mRNAs and play important roles in plant growth and development and abiotic stress resistance. Longan (Dimocarpous longan) is a tropical/subtropical fruit tree of great economic importance in Southeast Asia. However, genomic information on C3H and their functions in longan are still unknown. In this study, a comprehensive analysis of the longan C3H (DlC3H) gene family was carried out. A total of 49 DlC3H genes in three clades were identified from the longan genome database. Characteristics of the genes were analyzed with respect to gene structure, motif composition, phylogenetic tree and potential functions. The analysis of alternative splicing (AS) events suggested that AS events in DlC3H genes were related to the transformation from longan non-embryonic to embryonic cultures. Promoter analysis indicated that most of the DlC3H genes included cis-acting elements associated with hormones and stresses responses. Quantitative real-time PCR (qRT-PCR) analysis indicated that 26 of the 49 DlC3Hs, which possess methyl jasmonate (MeJA) and abscisic acid (ABA) responsive cis-acting elements, showed differential expression patterns under treatment with ABA, MeJA and their endogenous inhibitors, suggesting that DlC3Hs might be involved in the ABA and MeJA signaling pathways. The expression profiles of 17 of the 49 DlC3Hs in non-embryonic callus and three tissues of embryonic cultures showed that only five of the 17 DlC3Hs had the same expression trends as the FPKM trends in transcriptome data; the expression levels of DlC3H07/14/16/36/49 in embryogenic callus and DlC3H04/38 in globular embryos were high, suggesting that they have different functions in embryonic development. Further, we verified that DlC3H01/03/05/11/19/39 were regulated by sRNAs by a modified 5′ RLM-RACE method. This study provides the first systematic analysis of C3H genes in longan, and found that C3H genes may be involved in hormone and stress responses, and somatic embryogenesis. Our preliminary investigation may provide clues to further studies on the characteristics and functions of this family in longan.